INTRODUCING DIGITAL TECHNOLOGIES TO STUDENTS AT THE PRIMARY LEVEL OF EDUCATION. ("Conference on Universal Science Research 2023", 2023)
The methods used by different schools of speech analysis are very different. In particular, the analysis of everyday dialogue and works of Chafe is based on natural speech materials. At the same time, in the analysis of everyday dialogue, generalizations are obtained by identifying recurring, dominant patterns, and Chaf prefers the method of introspection. In Tomlin's works, the empirical material consists of experimental rather than natural data, and the processing of the material involves the standard use of statistical tests for cognitive psychology.